Effect of pedestal fluctuation on ELM frequency in the EAST tokamak. (16th March 2018) - Zhong, F.B.; Zhang, T.; Liu, Z.X.; Qu, H.; Liu, H.Q.; Li, G.Q.; Liu, Y.; Gao, W.; Duan, Y.M.; Yang, Y.; Zeng, L.; Xiang, H.M.; et al.
Abstract: The dependence of ELM frequency on heating power has been studied on the Experimental Advanced Superconducting Tokamak (EAST). It is found that the ELM frequency ( f ELM ) generally increases with the power through separatrix ( P sep ), indicating type-I ELM in these plasmas. However, there are two data points, named 'abnormal ELM' in the present paper, which have much lower f ELM than the 'normal ELM', while both types of ELM have similar ELM energy losses. The 'abnormal ELM' occurs at a phase with increased radiation power due to metal impurity influx events. The increased radiation power cannot explain the much lower f ELM for 'abnormal ELM', since the reduction of P sep is weaker than proportional to the observed reduction of the ELM frequency. The 'abnormal ELM' feature can be attributed to the enhanced amplitude of a coherent mode in the pedestal region. Comparing the pedestal evolutions for the two types of ELM with similar separatrix power P sep, it is actually found that the more pronounced pedestal coherent mode in the plasma with 'abnormal ELM' leads to a slower pressure pedestal recovery during the inter-ELM phase. This experimental result implies that the physical mechanism for 'abnormal ELM' is that the more pronounced pedestal fluctuation induces larger outward transport, slows down the pedestal evolution and leads to longer inter-ELM phase, i.e. lower ELM frequency.